Acoustic Emission Study Of Fatigue Crack Growth In Rail Track Material - Mohd Yusof, Taib (2010)

(untitled)
The fatigue crack growth behavior of longitudinal crack in rail steel was investigated using the compact tension, (CT) specimen. The fatigue crack growth rate curve, da/dN as a function of stress intensity factor range, ∆ K was plotted in order to analyze the crack growth properties of rail material. The CT specimen was tested by means of tension-tension stresses with load ratio of 0.1 while simultaneously recording the acoustic emission, (AE) signal. The acoustic emission count rate associated with the stress intensity factor was obtained to understand acoustic emission behavior corresponding to the fatigue crack growth. The result indicates that the constant values of C and m according to Paris Law equation, da/dN = C(∆ K) m are 2.63x10-12 and 3.29, respectively. The acoustic emission count rate equation becomes dn/dN = 2.63x10- 7(∆ K) 3.51. The linear relationship between crack growth rate and AE count rate will give log(da/dN) = 0.738log(dn/dN) - 5.815. Based on these correlations it may possible to monitoring fatigue damage of short term acoustic emission monitoring